Decoding the ESG Mandate: Examining the Impact of BRSR Regulations on HR, Marketing Practices, and Reporting in Leading Top 10 Indian Companies - Palagummi, Srividya (Digital Repository of Theses, 2026)
Since the topic of “Environmental, Social, and Governance” (ESG) reporting in India has been widely discussed, the introduction of the “Business Responsibility and Sustainability Reporting” (BRSR) framework by SEBI in 2022 is a big step forward in creating better systems for sustainable reporting. This framework requires companies to show how their actions impact the environment and society, and it also gives insight into how they make decisions. This is a new system that gives businesses chances to include sustainability in their work. But there are also some difficulties, especially in the areas of Human Resources (HR), marketing, and corporate reporting. The study picked the top 10 companies in India based on their market value. These companies work in different areas like IT, finance, consumer products, and telecommunications. The study uses descriptive statistics, regression models, and correlation tests to look at how following BRSR rules affects how well these companies do financially. The descriptive analysis shows that HR practices have advanced significantly, with a high acceptance rate of employee well-being programs and diversity efforts (M = 2.74, SD =0.44). However, leadership diversity remains limited, with women averaging only 20% of leadership roles despite comprising 39% of the workforce. Flexible policies for minorities (M = 3.12), mental health support (M = 3.10), and work-life balance programs (M = 3.18) underscore the growing emphasis of firms on employee well-being, while health programs score highest (M = 3.58), reflecting the post-pandemic shift. Marketing practices demonstrate a cautious adoption, with firms averaging nine ESG campaigns annually (M = 8.98). However, sustainability messaging in branding (M = 1.72) and green product promotion (M = 1.92) remain modest. Reporting practices show partial maturity, with limited ESG KPI disclosures (M = 1.72) but stronger depth of reporting (M = 2.66). Hypothesis testing confirms a significant alignment of HR practices with ESG outcomes (R² = 0.860, F = 21.297, p < .001), where leadership representation (β = 1.295, p < .001) and inclusion of under-represented groups (β = 0.512, p < 0.001) emerge as critical drivers. Marketing strategies that leverage ESG compliance positively influence on firm performance, with a model significance of F = 5.473, p = 0.045. Reporting practices, although weaker (R² = 0.175), indicate that normalisation scores significantly improve financial outcomes (B = 0.878, p = 0.045). Overall, the findings highlight that while Indian companies are embedding ESG into their HR, marketing, and reporting practices, structural gaps in leadership diversity, standardised reporting, and consistent marketing integration persist. ESG adoption under BRSR demonstrates positive financial and strategic implications, signalling a transformative yet evolving shift in corporate sustainability practices. Keywords: Business Responsibility and Sustainability Reporting (BRSR), Environmental, Social, and Governance (ESG), Human Resource (HR), Marketing, Corporate Reporting.